Perforated Retroperitoneal Appendicitis Presenting as Extensive Subcutaneous Emphysema of Abdominal and Chest Wall: An Unusual Presentation - Vishnu Kumar Patel; APS Gaharwar; Rohan S Batra; Umesh Patel (International Journal of Medical Research and Review, 2014)
Acute appendicitis is a commonly encountered disease in surgical practice. Timely diagnosis and management prevents morbidity and mortality from this disease. Acute appendicitis may occasionally become extraordinarily complicated and life threatening yet difficult to diagnose. This atypical presentation is rare and required high index of suspicion. We present a case report of perforated retroperitoneal appendicitis, which presented to us with extensive subcutaneous emphysema of back and chest wall with no abdominal signs.